Preparation and Characterization of Porous Polyacrylonitrile Materials via Concentrated Emulsion Template Method - Chang, Haitao; Gong, Xueyong; Zheng, Chao; Wei, Zhenhua (Asian Journal of Chemistry, 2014)
In this study, highly porous polyacrylonitrile materials have been prepared via concentrated emulsion template method. With the aid of colloidal silica nanoparticles added to the droplet phase stable concentrated emulsions had been obtained. To investigate their porous morphologies, the foams were characterized by scanning electron microscopy (SEM) and nitrogen adsorption. It was observed that silica nanoparticles acted as a cosurfactant, which was absorbed on the interface of the emulsion preventing the coalescence of the droplet phase. The cell diameters of polyacrylonitrile foams were controlled within a range of 1 to 10 μm by varying the emulsion composition. Nitrogen adsorption analysis showed that the resulting foams possessed mesoporous pore structures. Our method provides a facile route to fabricate highly porous polyacrylonitrile materials with controlled morphology.